(3TQM eNJUQ GdeRfis - (3WGgQ Hf YHO Gddg Hf WGgQ GdWHQj, CHh GdWqjH , (B450 (3g` s; (3GdeRfj , ESeGYjd Hf jMji Hf ESeGYjd, CHh EHQGgje,J (B264 (3g` s
(3ChdgG (B:s
(3HGH SLOJi GdSgh hGdTcQ s
(3BNQgG (B:s
(3HRcGI GdeGTjI s
(3gfGc TQM deNJUQ GdeGRfi HYfhGf GdMGhi deDda eLghds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs